Gastroenterological problems of bariatric surgery - Ekaterina Yu. Plotnikova; Gleb I. Kolpinsky; Irina N. Semenchuk (LLC "MEDIAFORMAT", 2023)
Dietary imbalances and overeating can lead to a common disease today - obesity. Apart from aesthetic considerations, obesity is defined as an excess of adipose tissue, which can lead to serious health problems and predispose to a number of pathological changes and clinical diseases such as diabetes, hypertension, atherosclerosis, coronary heart disease, obstructive sleep apnea, depression, arthropathy weight-related diseases, as well as endometrial and breast cancer. Body weight exceeding the ideal weight for age, sex and height by 20% poses a serious health risk. Bariatric surgery is a comprehensive surgical treatment for morbid obesity when other treatments such as diet, increased physical activity, behavior modification and medications have failed. The two most common procedures used today are sleeve gastrectomy and Roux-en-Y gastric bypass. These procedures have gained popularity recently and are generally considered safe and effective. The article describes common and standard disorders in the digestive system that occur after bariatric surgery. A clinical example of a patient's history after sleeve gastrectomy is also given, who was not observed and did not carry out the standard necessary postoperative measures.